Dinomyrmex gigas (Latreille, 1802): a potential icon for Taman Negara Johor Endau Rompin - H., Muhammad Shafiq; M., Maryati (2021)
Dinomyrmex gigas (Latreille, 1802) is one of the largest ants in the world and the largest in Southeast Asia. It is also more commonly known as the giant forest ant. This large charismatic ant can be found in the forests of Southeast Asia, however it is not often sighted by the public due to its predominant nocturnal nature. Despite being considerably well studied compared to its smaller counterparts, most people know little about the giant forest ant beyond its large size. Most studies on this species focus on the populations found in Malaysia and Brunei characterizing many aspects of the natural history and biology of this species including its foraging behaviour, diet, territoriality, reproduction and colony structure. While much is known about the biology of this species, fragmented forest habitats may have an impact on the viability and behaviour of this majestic giant ant of the forest. This study involved insects’ viability observation and sampling of ant specimens. The results of observations showed that D. gigas is viable in Endau Rompin Johor National Park (TNJER). Then, various ecological aspects of D. gigas was investigated through field studies and secondary information. Due to its size and uniqueness this species has a potential to be developed into a nature tourism product for Malaysia. The present study elaborated to further discover its daily activity, nesting and defence behaviour which could be useful in developing it into a nature tourism product. As the species is also limited in distribution to undisturbed forest, the issue of its survival is discussed with relation to conservation of the tropical rainforest.